2014
DOI: 10.1002/hlca.201300102
|View full text |Cite
|
Sign up to set email alerts
|

Two New Cytotoxic Spirostane‐Steroidal Saponins from the Roots of Bletilla striata

Abstract: Two new spirostane-steroidal saponins, bletilnoside A (1) and bletilnoside B (2), together with five known compounds, 3 -7, were isolated from the roots of Bletilla striata (Thunb.) Reichb. F. The structures of the new compounds were determined based on their 1D-and 2D-NMR spectral data. The isolated compounds 1 -7 were tested for cytotoxicity against four human tumor cells (A549, SK-OV-3, SK-MEL-2, and HCT15) in vitro using a sulforhodamin B bioassay, and compounds 1, 2, and 5 showed significant cytotoxicitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Thus, it has been used as a valuable hemostatic agent for the treatment of hemoptysis, vomiting blood, traumatic bleeding, and ulcerative carbuncles [4, 5]. Furthermore, it is not only used in the treatment of sores, chapped skin, and swelling [6, 7] but also has antibacterial [8, 9] and antitumor effects [1012]. After years of research, more than 90 compounds have been isolated from B. striata tubers, including benzyl compounds, phenanthrene, glycosides, anthocyanins, triterpenes, and steroids [10, 13–15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has been used as a valuable hemostatic agent for the treatment of hemoptysis, vomiting blood, traumatic bleeding, and ulcerative carbuncles [4, 5]. Furthermore, it is not only used in the treatment of sores, chapped skin, and swelling [6, 7] but also has antibacterial [8, 9] and antitumor effects [1012]. After years of research, more than 90 compounds have been isolated from B. striata tubers, including benzyl compounds, phenanthrene, glycosides, anthocyanins, triterpenes, and steroids [10, 13–15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is not only used in the treatment of sores, chapped skin, and swelling [6, 7] but also has antibacterial [8, 9] and antitumor effects [1012]. After years of research, more than 90 compounds have been isolated from B. striata tubers, including benzyl compounds, phenanthrene, glycosides, anthocyanins, triterpenes, and steroids [10, 13–15]. Moreover, our previous pharmacological work has confirmed that B. striata extract shows a hemostatic effect by promoting platelet aggregation [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the extensive analysis of COSY, HSQC, HMBC, and ROESY spectra, the 1 H and 13 C NMR signals of 1 were assigned as shown in Table . Comparison of the NMR data of 1 with those of neoruscogenin , suggested that 1 had the same substructure as neoruscogein in rings C, D, E, and F. Further structural information on 1 came from the inspection of the COSY spectrum, which demonstrated the presence of three isolated spin systems as shown in Figure a. The HMBC correlations between H 2 -4 and C-6, between H 3 -19 and C-1, between H-2β and C-10, and between H-7β and C-5 indicated rings A and B were connected via a C-1 to C-5 bond, which established a 5/7 ring system.…”
mentioning
confidence: 96%